Critical shoe contact area ratio for sliding on a tennis hard court - Goff, J. E.; Boswell, L.; Ura, D.; Kozy, M.; Carré, M. J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
Dimples have been used in the design of some modern tennis shoe outsoles to enhance sliding ability on hard courts. Experiments were performed with bespoke rubber samples possessing various numbers of holes, which served to simulate dimples in tennis shoe treads. The aim of the research was to assess the effect of contact area on sliding friction. As the ratio of holes to solid rubber increased, a critical ratio was reached whereby the static friction coefficient decreased by more than 11% for tread-to-court pressures comparable to real tennis play. Although this study analyzed bespoke rubber samples and not actual tennis shoe treads, shoe manufacturers should be interested in the existence of a critical dimple ratio that could aid them in the creation of tennis shoes suited for sliding on hard courts.